Analyzing the use of specialized palliative care in intensive care unit patients in Germany: a cross-sectional study - Christiane von Saß; Theresa Tenge; Birgitt van Oorschot; Dawid Pieper; Nicole Eisenmenger; Martin Heinze; Larissa Fink; Guido Michels; Martin Neukirchen; Marcel A. Kamp (BMC Palliative Care, 2025)
Abstract Background Despite rising importance of integration of palliative medicine in treating life-threatening illnesses in intensive care units (ICU), the extent remains unknown. Using billing data, we analysed the frequency of specialized palliative care use in ICU patients in Germany. Methods Billing data (2019 -2022) from the InEK was used in this cross-sectional study on all billed adult ICU cases. Data included case numbers, demographics, diagnoses, treatment procedures, ventilation (≥ 95 h), palliative care frequency. Results 61,591,299 adult cases were treated, 11.2% (6,912,316) requiring ICU and 499,262 (7.2%) needing long-term ventilation. 44.2% of all ICU cases and 36.2% of long-term ventilated patients were female (p < 0.0001). ICU mortality was 11.1%, long-term ventilation mortality was 38.8%; higher in men and patients aged ≥ 65 (p < 0.001). Leading diagnoses for ICU deaths: heart failure (6.9%), stroke (6.3%), sepsis (6.2%). 0.8% of ICU cases and 1.4% of long-term ventilated cases received specialized palliative care, with a higher proportion of females (p < 0.0001). Most palliative care patients were aged ≥ 65. Conclusion From 2019 to 2022, 11.2% of hospital cases required ICU-treatment. Despite suffering from life-threatening conditions and high mortality rates, less than 1% of all ICU cases and 1.4% of long-term ventilated cases received palliative care (differing sexes and ages). This highlights deficiencies in palliative care integration into ICUs to alleviate patients and their families suffering from complex needs. Implementing benchmarking could be beneficial in this process.